A theoretical study on N-phenyl-N?-(2-thienylmethylene)hydrazine - Yakuphanoğlu, Fahrettin; Atalay, Y.; Sekerci, M. (Pergamon-Elsevier Science Ltd, 2007)
The molecular geometry and vibrational frequencies of N-phenyl-AP-(2-thienyimethylene)hydrazine (C11H10N2S) have been calculated using Hartree-Fock and density functional method (B3LYP) with 6-31G(d) basis set. The optimized geometric bond lengths and angles obtained using HF and DFr (B3LYP) are in agreement with the experimental data. B3LYP method seems to be appropriate than HF method for the calculation of vibrational frequencies and geometrical parameters of the (C11H10N2S) compound. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: N-phenyl-N '-(2-thienylmethylene)hydrazine (C11H10N2S); IR spectra; DFT; HF